Shrinkage perceptions and smart growth strategies for the municipalities of Portugal - Panagopoulos, Thomas (2014)
In the last decade, several Portuguese municipalities have faced population decline. This paper systematises the most implemented strategies by the Portuguese governments and identifies their results in dealing with population decline. Based on a survey of the most important newspapers and municipality websites, and by using economic and demographic annual data for 10 years (1999–2008), it was found that the majority of the municipalities have implemented strategies of “smart growth” and “smart shrinkage”, while the others have presented a misperception of shrinkage. The resilience capability of each municipality, in the adaption of the activities of primary and secondary sectors into the tertiary sector, was identified as an important factor for the success of smart growth strategies.